Ontology Matching as Regression Problem- - Nadia Alboukaey; Ammar Joukhadar (Journal of Digital Information Management, 2018)
Ontology matching is one of the most important works to achieve the goal of the semantic web. To fulfill this task, element-level matching is an indispensable step to obtain the fundamental alignment. In element-level matching process, previous work generally utilizes multiple measures to compute the similarities among elements, and then combine these similarities using a weighted sum formula to determine later the semantic correspondences. The proper selection and combination of these similarities strongly influence the final quality of the matching system.

Ontology Matching as Regression Problem - Nadia Alboukaey; Ammar Joukhadar (Journal of Digital Information Management, 2018)